Gene of paper-making cholesterase, expression vector, strain and applications thereof - GAO SHIPENG; HAN SHUANGYAN; LIN YING; LI LING; ZHENG SUIPING (2017)
The invention discloses a gene of paper-making cholesterase, an expression vector, a strain and applications thereof, and belongs to the field of bioengineering. A nucleotide coding sequence of the gene is shown as SEQ ID NO:1. The cholesterase gene provided by the invention, on the basis of such technologies as codon optimization, escherichia coli expression, pichia pastoris expression and the like, achieves high expression in pichia pastoris; and the enzymatic activity of the obtained cholesterase is about 0.4U/mL. The expressed cholesterase has the properties of resisting high temperature and resisting weak base; the cholesterase provided by the invention can be applied to waste paper de-inking, namely ink particles can be removed by hydrolyzing adhesives on the surface of waste paper and between paper pieces; and the stable quality of recycled paper and the operating efficiency of a paper-making machine can be guaranteed. 本发明公开种造纸用甾醇脂酶的基因、表达载体、菌株及其应用，属于生物工程领域。该基因的核苷酸编码序列如SEQ ID NO：1所示。本发明提供的甾醇脂酶基因利用密码子优化、